TRANSLATION INTERNAL FEATURES OF LUINGUSTIC UNITS DESCRIBING THE PORTRAIT - Yuldosheva Mamura Bakhtiyarovna (Western European Studies, 2024)
Thiѕ artiсlе iѕ dеvоtеd tо describe the psychological portrait of the heroes, which the writer tries to hide the character of the hero through his appearance. In fiction, the image of a person, his working mental states, thoughts, tragic, sad, happy lifestyle is the first place. The personal conservancy strives to get rich and get rich, to approach a person in every way, to show his spiritual world with its bright and beautiful sides. The re-estimation of realistic factors, artistic researches made it possible for the world of expression of word art to be realized in a colorful way. The object of our research work is the analysis of linguistic units describing the portrait of an artistic hero, and the novel "Bygone days" by A. Qadiri and different versions of its translation into English were chosen as the research material. and the stylistic features of English as the translation language, we need to understand the similarities and differences between them
Keywords: portrait; description; artistic features